Kemampuan Memahami Teks Prosedur Siswa Kelas VII Pesantren Thawalib Padang - Suci Pitaloka; Dina Ramadhanti; Asri Wahyuni Sari (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2023)
The purpose of this study was to describe the ability to understand procedural texts for class VII students of the Padang Thawalib Islamic Boarding School. This type of research is quantitative. This research method is descriptive method. The subjects of this study were class VII students at the Thawalib Padang Islamic Boarding School who were enrolled in 2022/2023 with a total of 58 people. The instrument used in this study is a multiple choice test. The data analysis technique used in this study was to analyze the data obtained from the structure and language reading tests of students' procedural texts by reading and checking student work according to the grid studied, then processing scores into scores using the percentage formula. The next step is to classify students' ability to read procedural texts by using the ability to understand grade VII students of the Thawalib Islamic Boarding School in Padang using a scale of 10. Presenting the values ??obtained into a frequency distribution table. Finally discuss the results of the analysis and make conclusions. The result of this research is that students' ability to understand procedural text is good enough, this can be seen from the results obtained by students.